DIGITIZATION PROBLEMS AND PERSPECTIVES IN SUPPLY CHAINS IN CONTEXT OF INDUSTRY 4.0 CHALLANGES - Raimonda, Sudziuviene; Indre, Sudziute; Grazina, Beniusiene; Danguole, Jukniene (SWorldJournal, 2024)
The Fourth Industrial Revolution has been going on for a good 10-20 years and nobody can name the specific beginning. Industry 4.0 is a new economical development stage, featuring technologies such as big data, artificial intelligence, the Internet of thi